The Effect of Board Independence, Gender Diversity and Board Size on Firm Performance in Malaysia - Abdullah, Shamsul Nahar; Aziz, Azbariyah; Azani, Aizulfithri (Journal of Social Economics Research, 2022)
The aim of this research is to investigate the effects of corporate governance characteristics on a company’s financial performance. To this end, board independence, board gender composition and board size were tested to determine whether they have any influence on a firm’s financial performance. Given the high concentration of ownership in listed companies in Malaysia and the prevalence of family ownership, this research provides evidence from an emerging market. The Malaysian Code on Corporate Governance (MCCG) was developed based on the UK Hampel Report and the UK Corporate Governance Code, where firm ownership structure is dispersed and family ownership is prevalent. A sample of 70 randomly selected publicly listed companies in Malaysia over the period from 2016 to 2020 was used in this study. From a multiple regression analysis, the results showed that board independence, board gender composition and board size are positively and significantly associated with financial performance; therefore, appointing more independent directors, appointing female directors to the board and appointing more directors to the board leads to higher financial performance. Hence, the initiative by the Malaysian government to mandate listed firms to have a board that comprises at least 30% women does have a business case.